Faktory ovlivňující CSR reportování - Kašparová, Klára, 1978- (Masarykova univerzita, Ekonomicko-správní fakulta, 2012)
CSR reporting currently represents one of the most rapidly growing areas of CSR. It can be characterized as a process of communication of social and environmental impacts of corporate activities on the selected types of stakeholders. Motivation of corporate managers to its utilization can be explained by several theories. The book describes in detail three most frequently mentioned theories - the legitimacy theory, the positive accounting theory, and the stakeholder theory. On their basis foreign researchers identified a number of factors influencing the CSR reporting. Findings of their impact.